1980
DOI: 10.1172/jci109740
|View full text |Cite
|
Sign up to set email alerts
|

Selective noncompetitive assimilation of bovine testicular beta-galactosidase and bovine liver beta-glucuronidase by generalized gangliosidosis fibroblasts.

Abstract: A B S T R A C T Bovine liver /3-glucuronidase and testicular /3-galactosidase were assimilated by generalized gangliosidosis fibroblasts at respective rates of 90 and 464 times the rate of assimilation of horseradish peroxidase. Assimilation of either of the two enzymes by the fibroblasts was saturable, suggesting the participation of receptor-mediated adsorptive endocytosis for internalization. The rate of assimilation of either enzyme was not affected by high levels of the other enzyme, suggesting that disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Kinetic studies suggested that the endocytosis of acid hydrolases fulfills two requirements for a receptormediated, active transport process [6,[11][12][13][14][15][16][17][18][19]. First, selectivity was evident from rides (which were susceptible to degradation by alkaline phosphatase, a-mannosidase, and 0-N-acetylglucosaminidase) following endoglycosidase H treatment of high uptake a-N-acetylglucosaminidase.…”
Section: Evidence For Phosphorylmannose In the "Common Recognition Mamentioning
confidence: 99%
“…Kinetic studies suggested that the endocytosis of acid hydrolases fulfills two requirements for a receptormediated, active transport process [6,[11][12][13][14][15][16][17][18][19]. First, selectivity was evident from rides (which were susceptible to degradation by alkaline phosphatase, a-mannosidase, and 0-N-acetylglucosaminidase) following endoglycosidase H treatment of high uptake a-N-acetylglucosaminidase.…”
Section: Evidence For Phosphorylmannose In the "Common Recognition Mamentioning
confidence: 99%
“…proved to be acid hydrolases that were secreted into the culture medium by fibroblasts and were also present in body fluids and tissue extracts . The selectivity and saturability of the uptake system suggested a receptor-mediated uptake process (9,10,16,19,30) . I-cell disease fibroblasts, which were characterized by a deficiency for multiple lysosomal enzymes, were found to secrete enzymes into the extracellular fluid that were not susceptible to pinocytosis by normal fibroblasts .…”
mentioning
confidence: 99%
“…The more anionic, higher binding (14). Uptake of the pooled fractions by generalized gangliosidosis skin fibroblasts was performed as previously described (13). Both binding and uptake studies were performed with the subsaturating concentrations of &galactosidase indicated in the footnotes.…”
Section: Resultsmentioning
confidence: 99%
“…After 3 h of exposure the cells were scraped from the plates, dispersed, and washed in saline. Enzyme activity was determined after disruption by freezing and thawing (13). Cell protein was determined by the procedure of Lowry (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation